Effects of balance electrode in deep micro-holes drilling in "nickel plate" through µECM process using H2SO4 electrolyte. (2021) - Rahman, Md. Zishanur; Das, Alok Kumar; Chattopadhyaya, Somnath
Abstract: Drilling of high aspect ratio taper-less micro-holes in hard to machine and exotic materials is very challenging field. Electrochemical micro-machining (μECM) is one of the cost-effective process and a better alternative for drilling of deep micro-holes in difficult to cut materials with precise dimension and good surface finish. Quality of deep micro-holes fabrication through µECM is highly influenced by electrolyte material and its concentration as well as balance electrode. In this study, H2 SO4 electrolyte (aqueous) is used for the analysis of deep micro-holes drilling in "nickel plate" through µECM process using circular balance electrode. Taguchi technique is used to optimize the machining parameters and ANOVA is applied to investigate the effects of these parameters on the response outputs such as average diameter, overcut and diameter difference. The dominant machining parameters for the responses have been found out and the regression models have been developed. In last, all the experimental results obtained using balanced electrode have been compared with results obtained without using balance electrode at same machining conditions.